Therapeutic itinerary of people with leprosy: paths, struggles, and challenges in the search for care - Eliziane Oliveira de Lima; Maria Rocineide Ferreira da Silva; Mirna Neyara Alexandre de Sá Barreto Marinho; Olga Maria de Alencar; Thayza Miranda Pereira; Lúcia Conde de Oliveira; Saiwori de Jesus Silva Bezerra dos Anjos
ABSTRACT Objectives: to understand how the therapeutic itineraries of people affected by leprosy are processed. Methods: this is a descriptive, qualitative study, conducted in April 2018 in Barão de Grajaú in Maranhão, with interviews in the form of narratives of seven patients who had a late leprosy diagnosis. Results: the search for diagnosis is a major difficulty in accessing health services, resulting in a late diagnosis and, consequently, with the presence of visible deformities. It was noticed that the health units do not have a flow, nor protocols for comprehensive treatment, and these people are referred to a referral unit in another state to perform sputum smear microscopy. Final Considerations: leprosy control actions need reformulations that seek the relationship between operational activities, epidemiological indicators and risk factors, in accordance with the real needs of each region, thus highlighting the gaps evidenced in the therapeutic itineraries.